Euryhaline Hydrogel with Constant Swelling and Salinity‐Enhanced Mechanical Strength in a Wide Salinity Range. (20th October 2020) - Gao, Hainan; Mao, Jiale; Cai, Yudong; Li, Shuhong; Fu, Ye; Liu, Xiaolan; Liang, Haiyan; Zhao, Tianyi; Liu, Mingjie; Jiang, Lei
Abstract: In nature, many biological organisms possess a unique osmoregulation feature that enables them to survive in environments of different salinity, which is called euryhaline characteristics (e.g., salmon that can survive in freshwater and seawater). Drawing inspiration from these salinity‐tolerant organisms, here a strategy that integrates two polymer chain segments with different salinity tolerances is reported to produce a euryhaline hydrogel with stable water retention, constant swelling properties, superoleophobicity, and low‐adhesion to oil in aqueous environments over a wide range of salinity. The formation of internal dynamic complementary crosslinks is a key structural factor of the euryhaline attributes. The euryhaline hydrogel‐coated meshes can be successfully utilized in various oil/aqueous phase separation in a wide range of salinity. Furthermore, by creating a double network with dynamic bonds, superior euryhaline hydrogel with unique salinity‐enhanced mechanical strength can be obtained. It is anticipated that the euryhaline hydrogel will have broad application prospects in complex and variable ionic environments. Abstract : Drawing inspiration from euryhaline organisms in nature, a strategy of constructing euryhaline hydrogel with internal dynamic complementary cross‐links is reported, to produce stable water retention, constant swelling properties, superoleophobicity, and low adhesion to oil in aqueous environments over a wide range of salinity.